ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PERSONIL KEPOLISIAN - Tony Wijaya; S. Pantja Djati (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2007)
This research aims to know the influence of variable of organizational citizenship behavior (OCB) consist of compliance, participation, and loyalty simultaneously and partially to personnel of police performance. The analysis used in this research is multiple regression analysis. This research uses 70 respondents. Pursuant to result of research indicate that variable of organizational citizenship behavior consist of compliance, participation, and loyalty have an influence to performance of police personnel. Level of change of police personnel performance explained by compliance, participation, and loyalty variable is equal to 47% while other variable which explain variation of change of performance level of police personnel is equal to 53%. Most dominant factor that has an effect on to police personnel performance is participation.